Innovative priorities of structural reorganization of the industry - Зубарєв, В.В. (Proceedings of National Aviation University (archive), 2012)
The article observer the priorities and directions of structure innovation models improvement for the development of industry. The role of scientific and technical potential in rise of Ukrainian’s economy is shown